Maternal, infant and placental size at birth : a study of firstborn, term infants and their mothers in Cape Town - Woods, David Lawrance (Department of Paediatrics and Child Health, 2018)
This study was conducted to document the size of primigravid women and their infants and placentas born at term in the Coloured community of Cape Town. It also explored the relationship between maternal, infant and placental size at birth. One thousand nine hundred and fifty seven firstborn infants delivered at term to Coloured women by the Peninsula Maternity Service during 1975 and 1976 were examined. The birth weight, crown-heel length and head circumference of each infant were measured, the gestational age assessed and the ponderal index of weight to length calculated. In addition the standing height, delivery weight and postdelivery weight of 395 of their mothers were measured and the Quetelet index of weight to height determined. The trimmed weight and chorionic plate area of 992 of the study infants' placentas were also measured and the placental thickness calculated.